Improving Learning Outcomes Of Class X Students In Mathematics Learning At SMA Negeri 2 Medan Through The Group Investigation (GI) Type Cooperative Model - Tasya Natali Sihombing; Pargaulan Siagian (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to improve student learning outcomes in mathematics class X MIPA 2 at SMA Negeri 2 Medan using the Group Investigation learning model. This research is a class action research. The subjects of this study were students of class X MIPA 2 with a total of 36 students. This research consisted of two cycles with two meetings in each cycle. Each meeting carried out a test of learning outcomes. Data collection techniques used learning achievement tests, observation sheets and student response questionnaires. Data analysis techniques use data reduction and data exposure. The results of this study indicate that the application of the Group Investigation learning model in mathematics learning can improve student learning outcomes in class X MIPA 2. This increase in learning outcomes can be seen from student contributions during the learning process in the form of student learning outcomes tests, students pay attention to the teacher's explanation, students express opinions , students work with groups, student responses to the use of learning models and the results of observations. The increase in classical completeness on the learning outcomes test I cycle I was 19.44%. Meanwhile, learning outcomes II in cycle I increased to 44.44%. In cycle II, the classical completeness test III of 86.11% increased to 94.44% in the fourth learning achievement test. The observation results showed that in the first cycle it increased from 3.54 to 3.73 in the very good category and the student response to learning using the Group Investigation model in the first cycle was 85% increasing to 90% in the second cycle. It can be concluded that almost all students in class X MIPA 2 gave a positive response and accepted the implementation of the Group Investigation learning model in class X MIPA 2. Based on the results of this study it can be concluded that the Group Investigation Learning Model can improve student learning outcomes in Mathematics Learning at SMA Negeri 2 Medan.